Evaluation of simple and rapid DNA extraction methods for molecular identification of fungi using the ITS regions - Wingfield, Lakkhana K.; Atcharawiriyakul, Jirawalun (Asia-Pacific Journal of Science and Technology, 2021)
Routine DNA extraction method previously used in our laboratory usually involved cetyl trimethyl ammonium bromide and phenol/chloroform extraction which was entirely time-consuming and cost-ineffective especially when performed large-scale species identification. The aim of the study was thus to evaluate alternative, simple and cost-effective methods for extracting DNA from filamentous fungi and mushrooms isolated from various environmental samples. Five simple and rapid methods for extracting DNA were evaluated for molecular identification. Each method was assessed based on PCR amplification of the ITS regions, measurement of yield and purity of extracted DNA including time required in the procedures. Method previously developed by the International Rice Research Institute (IRRI) was the best method for extracting fungal DNA. Meanwhile the IRRI and the sodium hydroxide-Tris (NaOH-Tris) methods were the best two methods that produced identical PCR amplification results from most samples (PCR efficiency of 85% and 89%, respectively). However, the NaOH-Tris method was superior to the IRRI method as it required short extraction procedure, reduced the need of using hazardous chemicals and was cost-effective. In contrast, ultra-simple, TE buffer and water methods were not effective for most fungal genera. We thus propose that the IRRI and NaOH-Tris methods were effective for rapid DNA isolation of large numbers of fungal cultures, specially replacing the use of conventional DNA extraction procedures. In addition, these methods can be applied to diverse fungal genera isolated from various environmental sources for fungal population and molecular studies.